2006
DOI: 10.2478/s11756-006-0053-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of brassinosteroid on cotton regeneration via somatic embryogenesis

Abstract: Brassinolide (BR), which is the most biologically active brassinosteroid, was used to examine the potential effect of hormone on cotton somatic embryogenesis. Ten-day-old cotton (Gossypium hirsutum L., cv. Cooker) seedlings were used for explant source and hypocotyls were removed and cultured on MS basal medium with B5 vitamins supplemented with 1 mg/L 6-benzylaminopurine + 0.5 mg/L kinetin for callus induction. After one month proliferating calli pieces were collected and cultured on MS basal medium containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…BL along with IAA and BA increased shoot regeneration and shoot height in Spartina patens (Lu et al 2003). BR stimulated somatic embryogenesis in cotton (Aydin et al 2006). BRs increased protein content and CAT and SOD activity in Brassica juncea L. under field conditions (Sirhindi et al 2009).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…BL along with IAA and BA increased shoot regeneration and shoot height in Spartina patens (Lu et al 2003). BR stimulated somatic embryogenesis in cotton (Aydin et al 2006). BRs increased protein content and CAT and SOD activity in Brassica juncea L. under field conditions (Sirhindi et al 2009).…”
Section: Discussionmentioning
confidence: 93%
“…BL along with indole-3-acetic acid (IAA) and 6-benzylaminopurine (BA) increased callus fresh and dry weight in Spartina patens, a halophyte monocot (Lu et al 2003). BR treatment was also negatively effective on the fresh weight of calli in cotton (Aydin et al 2006). BL along with IAA and BA increased shoot regeneration and shoot height in Spartina patens (Lu et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, based on the signalling pattern, Br signalling in plants has been correlated with metazoan Wnt like signalling. It is reported that Br is involved in the process of callusing, somatic embryogenesis 82 and promotes fibre initiation and elongation in Gossypium 83,84 . This role of Br is rather comparable to that of Wnt's action in animals where Wnt promotes embryogenesis and cell reprogramming.…”
Section: Wnt Signalling In Gossypium!!mentioning
confidence: 99%
“…Different kinds of plant growth regulators are needed in different stage of bamboo regeneration, and auxin and cytokinin are the critical components for the morphogenesis in vitro. Besides, ethylene, abscisic acid (ABA) and brassinosteroid (BR) will also have different effects on embryogenesis and organogenesis (Aydin et al, 2006;Torrizo & Zapata, 1986;Vain et al, 1989).…”
Section: Selection Of Mediamentioning
confidence: 99%